Relations between literature and soccer: «O míster & Iron Maiden», by Manuel Rivas - Rivero Grandoso, Javier (Madrygal. Revista de Estudios Gallegos, 2014)
Traditionally, soccer and literature have been arranged in two separated fields, especially because of the prejudices between them. No many examples exist that connect this sport with arts. Nevertheless, writers are paying more attention to soccer nowadays, by including this topic in the journalistic articles or even in fiction texts. For this paper I seek to analyze a chase of Galician sport and literature: the short story “O mister & Iron Maiden”, by Manuel Rivas, where the Deportivo de la Coruña’s coach, Arsenio Iglesias, plays an important role.
Keywords: literature and soccer; literature and football; Manuel Rivas; Arsenio Iglesias; Real Club Deportivo de la Coruña; “O míster & Iron Maiden”.